Perancangan Game Virus Survivor Untuk Pendidikan Kesehatan Dengan Metode Game Development Life Cycle - Bagus Fikri Ananda; Ahmad Chusyairi (Puslitbang Sekawan Institute Nusa Tenggara, 2019)
In urban areas found there are dirty so that the virus can develop and produce disease. To cope with the disease, an immune or immune system is needed. One prevention against viruses is by treatment in pill or other forms. Education about health about viruses is very much needed by the community, especially early childhood so that education can be interesting and interactive so it is made in the form of educational games. The purpose of this study is to provide health education to users to care about health, remind users of the importance of maintaining the health of viruses or microbes or the like where prevention is better than cure, avoiding dirty or dirty places, giving knowledge about places that are often occupied by viruses, and care about the environment by maintaining environmental cleanliness. The method used in this study is The Games Development Life Cycle. Buildbox is one of the tools used in making games that are user-friendly or easy to use. The virus survivor game explains about virus specialists who are required to pass dirty places in the city by avoiding viruses and obstacles that lead to the laboratory to make drugs in the form of pills to make the body become immune to the virus. The doctor must also collect coins in the form of DNA to open new characters to make them stronger. Power up to fight the virus in the form of an immune pill to make it immune to viruses, magnetic DNA pills to make it easier to get coins, and pills to eradicate the virus. The conclusion in this study is that the virus survivor game is an educational game to improve public health knowledge, especially early childhood so that the body is expected to have immunity to disease viruses.